Libelloidini, new name for an old tribe (Neuroptera Ascalaphidae) - Pantaleoni, Roberto A.; Loru, Laura (Zootaxa, 2018)
Almost a half century ago, Tjeder (1972) stated that the genus Ascalaphus had been interpreted in a sense other than that defined by its type species (see Pantaleoni and Loru 2018). So, the generic name Ascalaphus Fabricius, 1775, became the senior synonym of Helicomitus McLachlan, 1871, and the genus Libelloides, Schäffer, 1763, was reserved for the Palearctic diurnal coloured owlflies, which until then were considered to belong to the genus Ascalaphus. Even though Tjeder’s proposition produced a dramatic change in a long-term “prevailing usage”, it was immediately and universally accepted as necessary. However, surprisingly, this change was never followed by the consequent necessary nomenclatural changes at the family-group name level.